Effect of swab pooling on the Accula point-of-care RT-PCR for SARS-CoV-2 detection - Lancelot, Moira; Fibben, Kirby; Sullivan, Julie; O’Sick, William; McLendon, Kaleb; Wu, Huixia; Rao, Anuradha; Bassit, Leda C.; Greenleaf, Morgan; Miller, Pamela; Krull, Wolfgang; Tyburski, Erika; et al. (Frontiers in Microbiology, 2023)
Swab pooling may allow for more efficient use of point-of-care assays for SARS-CoV-2 detection in settings where widespread testing is warranted, but the effects of pooling on assay performance are not well described. We tested the Thermo-Fisher Accula rapid point-of-care RT-PCR platform with contrived pooled nasal swab specimens. We observed a higher limit of detection of 3,750 copies/swab in pooled specimens compared to 2,250 copies/swab in individual specimens. Assay performance appeared worse in a specimen with visible nasal mucous and debris, although performance was improved when using a standard laboratory mechanical pipette compared to the transfer pipette included in the assay kit. Clinicians and public health officials overseeing mass testing efforts must understand limitations and benefits of swab or sample pooling, including reduced assay performance from pooled specimens. We conclude that the Accula RT-PCR platform remains an attractive candidate assay for pooling strategies owing to the superior analytical sensitivity compared to most home use and point-of-care tests despite the inhibitory effects of pooled specimens we characterized.